Sistema de indicadores para la gestión de la calidad en la Universidad Técnica de Cotopaxi. - Vargas Torres, Ángel Patricio (2022)
Quality is known as the predictable degree of uniformity and reliability based on reducing costs and consolidating profits in an organization. This paper aims to propose quality through indicators to improve educational and financial processes seeking to satisfy the student body in order to improve the learning. It is practically conditioning a series of elements and internal and external components with a view to strengthening continuous improvements. One of these components that positively influence to support the processes They are quality management indicators recognized as measurement tools or instruments, of a tangible and quantifiable nature, which are based on evaluating the quality of processes, products/services that ensure customer satisfaction. The objective of this development project is to design a system of indicators for quality management at the Technical University of Cotopaxi, with the purpose of improving decision making at the different management levels. The methodological approach is qualitative with a descriptive and exploratory scope, based on the benefits offered by the balanced scorecard to propose indicators that help strengthen the activities of the institution. The results indicate that the simple fact of recognizing certain weaknesses in university tasks gives the opportunity to structure indicators that allow both the teaching and administrative staff and students to have a response capacity according to the requirements of the institution. The conclusions lead that the quality in accordance with the management indicators merged with the balanced scorecard, offer the Cotopaxi Technical University, continuous operational improvements in order to become a pioneer in this type of changes that pushes them towards excellence.